Jordan : Report on the Observance of Standards and Codes (ROSC)-Data Module. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2002)
This Report on the Observance of Standards and Codes (ROSC) provides a review of Jordan's data dissemination practices against the IMF's General Data Dissemination System (GDDS), complemented by an in-depth assessment of quality of national accounts, consumer and producer price indices, and government finance, monetary, and balance-of-payments statistics. The assessment reveals that Jordan participates in the GDDS and meets the recommendations for the coverage, periodicity, and timeliness of most data categories. Jordan's macroeconomic statistics also broadly meet the periodicity requirements of the SDDS.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet